Discrediting Accreditation?: Antitrust and Legal Education - Marina Lao (Washington University Law Quarterly, 2001)
This Article addresses the major antitrust issues concerning ABA accreditation. The first issue pertains to the reach of the unsettled state action and petitioning immunity doctrines, and the First Amendment. The analysis of state action and petitioning immunity draws a distinction between restraint on competition flowing from decisions to grant or deny accreditation and their associated state use on the one hand, and restraints on competition emanating from the accreditation standards themselves on the other. This Article concludes that, though the decisions may be immunized, neither doctrine clearly exempts restraints resulting from the accreditation standards from antitrust liability. With respect to the First Amendment defense, this Article takes issue both with the characterization of accreditation as mere speech and with the view that the First Amendment absolutely protects pure speech effectuating a restraint on competition. This Article proceeds as follows: Part II briefly describes the ABA accreditation system, without detailed reference to specific procedures or standards. Part III then analyzes the scope of the antitrust state action and petitioning immunity doctrines, and the First Amendment free speech clause as it relates to accreditation practices. Part IV develops arguments for concluding that the ABA accreditation system is anticompetitive. And Part V concludes by noting that, even if the current accreditation system can withstand an antitrust challenge, relaxing the ABA’s accreditation standards is desirable for policy reasons.
Keywords: Bar associations; Law schools -- Accreditation; Freedom of speech; Antitrust law exemptions; Right of petition; American Bar Association; Accreditation (Education); State action (Antitrust law)